A Narrative Review on Preclinical/Clinical Trials on Aducanumab - Goel, Akriti; Garima; Jain, Paras; Bansal, Seema; Chopra, Hitesh; Gupta, Sumeet; Kumar, Satish; Dhanawat, Meenakshi; Aggarwal, Navidha (Scripta Medica, 2026)
The most widespread type of dementia, Alzheimer's disease (AD), is predicted to triple in global prevalence by 2050. AD has a substantial societal and economic impact across the world, negatively affecting both patients and their caregivers, as the disorder has few therapeutic alternatives. Aducanumab was the first monoclonal antibody approved in 2021 for the treatment of mild AD. Representing the first AD drug approval in 20 years and based on the concept of targeting amyloid-β (Aβ) as an immunisation treatment for AD, Aducanumab was demonstrated to reduce Aβ plaque formation in animal models and humans. This was used as a proxy of efficacy in AD clinical trials to slow disease progression and reduce cognitive decline in AD. Culminating from the Aβ hypothesis of AD that has dominated the focus of AD drug development since its inception, Aducanumab, for many, represents validation of the hypothesis and promise for the future. This review examines the antibody research, preclinical and clinical studies, that underpin the development of aducanumab as an AD medication. No single drug is generally likely to cure a complex, progressive and heterogeneous degenerative disorder, but it may act as a stepping stone towards greater understanding and potentially more effective treatment options. Time will ultimately tell in the case of aducanumab as to whether it is a small or large step in the correct or incorrect direction to unravel the mystery of this complex disorder and provide a worthwhile treatment.
Keywords: Aducanumab; Alzheimer’s disease; Amyloid beta-peptides; Anti-dementia agents; Dementia; Antibodies, monoclonal